A COMPREHENSIVE STUDY OF GENERATION, TRAPPING AND OPTIMIZED PRODUCTION OF COAL BED METHANE (CBM). - TUNIO, SALEEM QADIR (2014)
The Coal Bed Methane (CBM) production commitment IS a maJor Issue because generation, trapping and optimization are all problematic issues for the exploration and development of the field. The main objectives of this work are to study the actual source of methane generation in CBM fields together with its trapping mechanism and also the optimization of CBM production based on variable permeabilities, different gas injection rate simulations for selected fields. Generation of methane, by default, is assumed to be coal itself but results suggest coal does not have sufficient hydrogen to generate commercial methane. Moreover, most of the producing CBM fields are associated with some petroliferous basin suggesting methane in CBM field may have intimate genetic relation with subsurface kerogen in the source rock. Attempts have been made here to compare characteristics of CBM and non-CBM coals.